The unbeatable Squirrel Girl. Vol. 2 Squirrel you know it's true - North, Ryan 1980-; Henderson, Erica; Renzi, Rico; Cowles, Clayton (New York, NY Marvel Worldwide, Inc., a subsidary of Marvel Entertainment, LLC, 2015)
"Squirrel Girl meets potential new allies, including Chipmunk Hunk, Koi Boi and...Girl Squirrel?! Yes! But the two rodent-themed heroines don't quite see eye-to-beady-eye-- and Squirrel Girl's dislike might be justified! Now, as the world goes mad and the Avengers attack, Squirrel Girl must face Ratatoskr, the Norse god of squirrels! There's a theme in this book, I don't know if you can tell. The fate of the world hangs in the balance, though, we promise. Featuring fights! Feelings! Sass! Punches! Friendship! A character named Hippo who is literally a hippo! And several tails (tales) of Squirrel Girl from all kinds of perspectives!"--Unedited summary from book.
"Contains material originally published in magazine form as The Unbeatable Squirrel Girl #5-8, GLX-mas Christmas special #1, The Thing #8 and Age of heroes #3."
UCWS-3151g donated by Eric Manalastas & Rommel Sta. Ana - July 2017
Keywords: Women superheroes -- Comic books, strips, etc; Good and evil -- Comic books, strips, etc; Graphic novels; Comics (Graphic works); Superhero comic books, strips, etc